FICTIONALIZING HISTORY: VIDYASAGAR NARZARY’S MALOTINI DAO MWINA - Narzary, Jitendra; Patra, Pradip Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Vidyasagar Narzary’s Malotini Dao Mwina occupies a critical position in Bodo literature as one of the first novels to blend history and fiction, focusing on the cultural and political events of the 15th century. It depicts the confrontation between the Kachari and Ahom kingdoms, centered around a love story between King Kumuri and Maloti, his love interest. The novel’s title, which includes the Myna bird (Mwina), serves as a symbolic representation of the interplay between personal and collective histories. While remaining faithful to historical truths, Narzary’s work reclaims and reimagines Bodo heritage, filling the gaps left by historical records and preserving oral traditions. The novel’s rich narrative draws from myths, geography, and Bodo cultural customs, intertwining them with the broader political landscape. Through imaginative storytelling, Narzary not only celebrates the essence of Bodo identity but also highlights the politics of representation. His work contributes significantly to literary studies by emphasizing the resilience, traditions, and agency of the Bodo people, transforming history into a powerful medium of cultural preservation and literary expression.